Energy Efficient Routing Protocols for Underwater Wireless Sensor Networks: A Review - Mukhtiar Ahmed; Mazleena Salleh; M. Ibrahim Channa; Mohd Foad Rohani (Universitas Ahmad Dahlan, 2017)
The Underwater Sensor Network (UWSN) is main interesting area due to its most valuable applications like: disaster preventions, distributed tactical surveillance, undersea exploration, seismic monitoring, environmental monitoring and many more. The design of energy efficient routing protocol is a challenging issue because in underwater environment the batteries of the sensor nodes cannot be recharged easily. Majority of the researchers have adapted the terrestrial WSN methodologies to overcome this problem but in underwater environment the terrestrial WSN approach is not feasible due to the acoustic signaling and water current. This research paper focuses the key limitation of the energy efficient routing protocols. The simulation results with comparative analysis for energy efficient routing protocols are also presented in this research article; which helps the researchers to find the further research gap in the field of energy efficient routing protocols.